1994
DOI: 10.1002/dev.420270105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CCK‐8 on ingestive behaviors of suckling and weanling rats

Dennis N. Lorenz

Abstract: The present series of experiments was designed to determine the dose-response characteristics of the cholecystokinin suppression effect on rat pups ingesting through suckling and adult modes. Pups at 10-22 days of age were deprived of their dam and food for 6 hr. At test time, the subjects received intraperitoneal injections or intravenous infusions of CCK-8 at 2, 4, 8, or 16 micrograms/kg in saline, or the saline vehicle alone. The pups were permitted to ingest for 30 min immediately after the injection or du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Using a similar paradigm, this study extends previous findings and demonstrates, for the first time, to our knowledge, that rat pups also develop reduced sensitivity to CCK when chronically eating a HF-diet. Numerous studies have shown that CCK or nutrients that stimulate CCK secretion are effective in reducing food intake in rat pups (9)(10)(11)(12)37). The CCK-1 receptor (CCK-1R) mediates these behavioral effects, because antagonism of the receptor attenuates nutrient-and CCK-induced satiation (12,37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a similar paradigm, this study extends previous findings and demonstrates, for the first time, to our knowledge, that rat pups also develop reduced sensitivity to CCK when chronically eating a HF-diet. Numerous studies have shown that CCK or nutrients that stimulate CCK secretion are effective in reducing food intake in rat pups (9)(10)(11)(12)37). The CCK-1 receptor (CCK-1R) mediates these behavioral effects, because antagonism of the receptor attenuates nutrient-and CCK-induced satiation (12,37).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined the relative time course for the development and extinction of reduced sensitivity to CCK-induced satiation in rats fed the HF diet. Rats used in the previous experiment (n = 8/group) adapted to LF and HF diets with mean body weights of 387 6 19.and 389 6 15.6 g, respectively, were fed their respective diets for an additional 3 wk (wk [8][9][10]. During this time (wk 9-10, phase I), the rats were tested for CCK sensitivity (0.25 and 0.5 g/kg) following the same protocol as described above.…”
Section: Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is evidence that both OT and CCK are involved in a variety of regulatory processes in infant rats. Exogenous administration of both CCK (Houpt & Houpt, 1979;Robinson, Moran, & McHugh, 1988) and OT (Nelson & Alberts, 1998, unpublished obs) reduce milk intakeÐalthough the CCK-induced reduction in ingestion is much stronger in the adult feeding mode than in the suckling mode (Lorenz, 1994). Furthermore, both of these substances have been shown to reduce USV emissions (Blass & Shide, 1993;Insel & Winslow, 1991;Weller & Blass, 1988) and to participate in odor preference formation (Nelson & Panksepp, 1996;Weller & Blass, 1988) in suckling rat pups.…”
Section: Discussionmentioning
confidence: 99%
“…In experiment one, the high pre-feeding levels of plasma CCK did not prevent the lambs from sucking. Although it has been suggested that CCK might be a factor regulating food intake in the new-born infant (Marchini and Linden, 1992) as it does in the adult (Crawley and Corwin, 1994), there is evidence in animal models that hunger mechanisms are not fully functional in the suckled young or do not involve CCK (Blass et al, 1979;Lorenz, 1994). In any case, CCK is unlikely to be a satiation factor in the young lamb since in experiment two most lambs stopped feeding before any increase was recorded in the plasma.…”
Section: Animalsmentioning
confidence: 99%